Antioxidant plasticity and thermal sensitivity in four types of Symbiodinium sp. Issue 6 (15th October 2014) - Krueger, Thomas; Becker, Susanne; Pontasch, Stefanie; Dove, Sophie; Hoegh‐Guldberg, Ove; Leggat, William; Fisher, Paul L.; Davy, Simon K.; Lin, S.
<x xml:space="preserve">Abstract</x> Warmer than average summer sea surface temperature is one of the main drivers for coral bleaching, which describes the loss of endosymbiotic dinoflagellates (genus: Symbiodinium) in reef‐building corals. Past research has established that oxidative stress in the symbiont plays an important part in the bleaching cascade. Corals hosting different genotypes of Symbiodinium may have varying thermal bleaching thresholds, but changes in the symbiont's antioxidant system that may accompany these differences have received less attention. This study shows that constitutive activity and up‐regulation of different parts of the antioxidant network under thermal stress differs between four Symbiodinium types in culture and that thermal susceptibility can be linked to glutathione redox homeostasis. In Symbiodinium B1, C1 and E, declining maximum quantum yield of PSII (Fv/Fm) and death at 33°C were generally associated with elevated superoxide dismutase (SOD) activity and a more oxidized glutathione pool. Symbiodinium F1 exhibited no decline in Fv/Fm or growth, but showed proportionally larger increases in ascorbate peroxidase (APX) activity and glutathione content (GSx), while maintaining GSx in a reduced state. Depressed growth in Symbiodinium B1 at a sublethal temperature of 29°C was associated with transiently increased APX activity and glutathione pool size, and an overall increase in glutathione reductase (GR) activity. The collapse of GR activity at 33°C, together with increased SOD, APX and glutathione S‐transferase activity, contributed to a strong oxidation of the glutathione pool with subsequent death. Integrating responses of multiple components of the antioxidant network highlights the importance of antioxidant plasticity in explaining type‐specific temperature responses in Symbiodinium.